EFEKTIFITAS TEKNIK SHAPING DALAM MENINGKATKAN KEMAMPUAN MENGENAL NAMA-NAMA BINATANG BAGI ANAK AUTIS X KELAS DII/C DI SLB PERWARI PADANG - Hanief Mahesa, Rahmatrisilvia, Ganda Sumekar (Universitas Negeri Padang, 2013)
This experiment in the background by an inability the son of autistic x class DII/C in SLB Perwari of Padang the field in know the names of animals so that he could not solve learning the Indonesian language. In this research target behavior is the capacity of children in know the names of the animal that is measured by the percentage of by using a technique of shaping. This research using the kind of research single subject research (SSR) with a design his research using design ABA and analyzed data analysis by using visual graphics. Research results are shaping effective technique to increase the son of autistic x class DII/C in SLB Perwari of Padang know the names of animals.